The Mathematics of Finance: Pricing Volatility derivatives - Phetpradap Parkpoom; Sripanitan Natkamon (ITM Web of Conferences)
In the increasingly complex world of financial markets, the scope of mathematical finance has expanded beyond traditional stock trading to include derivatives on various financial indices. The trading of stock derivatives has become commonplace across global markets. Furthermore, volatility derivatives, which are based on the volatility Index (VIX), have gained significant popularity in recent years. These instruments have been actively traded since the early 2000s. The objective of this article is to review some fundamental results on the pricing of basic volatility derivatives, under the Black-Scholes framework and other mathematical models.